Structural, electronic and vibrational properties of LaF3 according to density functional theory and Raman spectroscopy. (25th May 2018) - Oreshonkov, A S; Roginskii, E M; Krylov, A S; Ershov, A A; Voronov, V N
Abstract: Crystal structure of LaF3 single crystal is refined in tysonite-type trigonal unit cell P c 1 using density functional theory calculations and Raman spectroscopy. It is shown that trigonal structure with P c 1 space group is more energy-efficient than hexagonal structure with space group P 63 cm . Simulated Raman spectra obtained using LDA approximation is in much better agreement with experimental data than that obtained with PBE and PBEsol functionals of GGA. The calculated frequency value of silent mode B 2 in case of hexagonal structure P 63 cm was found to be imaginary (unstable mode), thus the energy surface obtains negative curvature with respect to the corresponding normal coordinates of the mode which leads to instability of the hexagonal structure in harmonic approximation. The A 1g line at 214 cm −1 in Raman spectra of LaF3 related to the translation of F2 ions along c axis can be connected with F2 ionic conductivity.